Kedudukan Hukum Putusan Arbitrase dalam Sengketa Kontrak Pengadaan Barang/Jasa Pemerintah terhadap Asas Kepentingan Umum - Pimal Ibrahim; Muhtadi; Kasmawati (Legalita, 2026)
This research examines the legal standing of arbitration awards in government goods and services procurement (PBJP) contract disputes, which often conflict with the principle of public interest and state asset immunity. The topic is chosen due to the “execution stagnation” phenomenon where government agencies frequently evade arbitration awards by citing the prohibition of state asset seizure. This study aims to analyze the executorial power of final and binding arbitration awards and to formulate regulatory synchronization between civil law and state financial law regimes. The methodology employed is normative legal research with statutory and conceptual approaches. The primary findings indicate that while arbitration awards are normatively binding, Article 50 of Law No. 1/2004 concerning the State Treasury often acts as a technical barrier that undermines legal certainty for providers. This research contributes by proposing a reconstruction of dispute payment mechanisms through contingency funds within the Budget Implementation List (DIPA) to avoid physical asset seizure. The study concludes that the protection of state assets must not negate contractual justice; regulatory synchronization is essential to maintain the investment climate and public trust in the national procurement system.